THE EDUCATIONAL ROLE OF THE COMPANIONS IN THE UMAYYAD ERA - Ahmed Hachim Kamil AL-Dhalimee (Journal of Higher Education and Academic Advancement, 2024)
After the matter was settled for Muawiyah bin Abi Sufyan, and the features of the stability of the state were established, the Caliph took the initiative to renew the movement of conquests that had stopped due to the events that occurred within the Islamic state and the dispute that took place over the caliphate. The movement of conquests returned with great momentum as a result of political and military stability, especially what he wanted. Muawiyah of Muawiyah conquered Constantinople and eliminated the capital of the Byzantine Empire in the Levant. To this end, Caliph Muawiyah bin Abi Sufyan spent money on developing Islamic warships, thus creating a war fleet capable of combating the Byzantine fleet that was imposing its control in the waters of the Mediterranean